AI-DRIVEN NUTRITIONAL ANALYSIS: ENHANCING DIETARY RECOMMENDATIONS THROUGH MACHINE LEARNING ALGORITHMS (International Journal of Food and Nutritional Sciences, 2021)
In an era where personalized healthcare is becoming increasingly significant, AI-driven nutritional analysis is emerging as a transformative tool to enhance dietary recommendations. This paper explores the integration of machine learning algorithms in nutritional analysis to provide tailored dietary recommendations that meet individual health needs. The study highlights how data from diverse sources, including dietary logs, medical histories, and real-time health metrics, can be utilized to build predictive models that optimize nutritional intake. By leveraging supervised learning techniques such as decision trees and support vector machines (SVM), the proposed system identifies patterns in nutritional data and predicts potential deficiencies or excesses. Additionally, unsupervised learning methods, including k-means clustering, are employed to segment populations based on dietary habits and health conditions, thereby enabling more targeted interventions. The research also delves into the use of deep learning algorithms for processing complex data sets, such as those obtained from wearable devices and IoT-based health monitors. These models not only enhance the accuracy of dietary recommendations but also adapt to changing health parameters, providing dynamic and real-time advice. The implications of AI-driven nutritional analysis extend to preventive healthcare, where early detection of nutritional imbalances can mitigate the risk of chronic diseases. This study presents a comprehensive overview of the potential and challenges of implementing AI in dietary recommendation systems, paving the way for more personalized and effective nutrition management strategies.